From propositional language to transcendental ethics in the Tractatus: the meaning and meaninglessness of utterances - Trinidad Felipe, Mishell (2025)
The article analyzes the problem of transcendental ethics in Wittgenstein’s work, particularly in the Tractatus Logico-Philosophicus. According to Wittgenstein, the meaning of propositions lies in their relation to facts, that is, in their capacity to represent true or false logical configurations. Statements that do not correspond to facts are situated outside the world and the logical space. In this framework, aphorism 6.421 states that ethics is transcendental because it does not address any facts of the world. Moral and value judgments, not being rooted in logical space, cannot constitute propositions in the Wittgensteinian sense. However, this does not imply that they lack meaning (sinnlos). On the contrary, such judgments influence the configuration of the facts that constitute the subject. The aim of the article is, therefore, twofold: first, to identify the meaning of moral and value judgments, and second, to distinguish it from the meaning of propositions. It is argued that, although ethical judgments are not inscribed in the logical space, they possess a meaning of their own that cannot be reduced or dismissed as insignificant.